Pollen morphology of some Silene L. (Caryophyllaceae) taxa distributed in Northwest Anatolia [Kuzeybati anadolu'da yayiliş gösteren bazi Silene L. (Caryophyllaceae) taksonlarinin polen morfolojisi] - (:unkn) unknown (My University, 1996)
The morphologies of pollen grains selected from 6 taxa belong to 3 sections [sect. Siphonomorpha Otth, sect. Elisanthe (Fenzl) Fenzl and sect. Silene] of the genus Silene L. (Caryophyllaceae) which were collected from the Northwest Anatolia [AZ(A), A3, A4, AS, A6] was investigated. The pollen grains were examined palynologically with the light microscope and scanning electron microscope (SEM) and were measured under Projectina screen scale microscope to obtain some morphological findings. All taxa that were examined are periporate (8-36 pores) and sphaeroidal. Their structure is tectate and semitectate; and the sculpture is spinulose (Microechinate), spinulose- microperforate and semireticulate. S. alba (Miller) Krause subsp. eriocalycina (Boiss.) Walters and S. noctiflora L. are semitectate and semireticulate; S. gallica L. and S. bellidifolia Jacq. which are tectate, spinulose-microperforate and have too many pores indicate that the taxonomical position of those taxa are correct. However, the taxonomical position of S. italica (L) Pers. and S. viridiflora L. may be discussed.
Keywords: Pollen morphology; Silene L.; Turkey